Sustainable Dimensions of Wellness Tourism: Exploring Environmental Sensitivity, Tourist Engagement, and Life Satisfaction - Karagianni, Vasiliki; Kalantonis, Petros; Tsartas, Paris; Sdrali, Despina (International Journal of Accounting and Economics Studies, 2025)
Wellness tourism is increasingly recognized as a sector that intersects personal well-being with sustainable tourism goals. This study examines the links between environmental sensitivity, tourist engagement, satisfaction, loyalty, and life satisfaction, focusing on wellness tourists in Greece. A structured survey was conducted to 487 visitors who had engaged in wellness tourism activities during the peak season. Key constructs were measured through validated scales, and the hypothesized relationships were tested using linear regression analysis. Findings reveal that environmentally sensitive tourists report higher satisfaction with wellness tourism and stronger loyalty intentions, underscoring the role of sustainability values in shaping consumer behavior. Frequent participation not only strengthens loyalty but also significantly enhances life satisfaction, suggesting that ongoing engagement produces cumulative well-being benefits. Moreover, satisfaction with wellness tourism positively predicts life satisfaction, confirming a spillover effect from tourism experiences to broader quality-of-life assessments. The results position wellness tourism as a strategic tool for sustainable development, capable of fostering ecological responsibility while delivering meaningful well-being outcomes. For Greece, leveraging its natural assets and wellness heritage through sustainable practices and loyalty-building strategies offers a competitive pathway to becoming a leading Mediterranean wellness destination. This research advances understanding by integrating environmental psychology, tourism behavior, and well-being theory into a unified empirical model, offering both conceptual insights and practical guidance for developing sustainability-aligned wellness tourism.
Keywords: environmental sensitivity; satisfaction; sustainable tourism; tourism; wellness tourism